THE EFFECT OFEMOTIONAL INTELLIGENCE ANDPERSONORGANIZATION FITTO AFFECTIVE COMMITMENT ONPT ADIRAFINANCE BANDAR LAMPUNG - Kurnia Fadila; Lusifika Indah Pratiwi; Besti Lilyana (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to examine the effect of Emotional Intelligence on Affective Commitment, Person-Organization Fit to Affective Commitment, and the effect of Emotional Intelligence and Person-Organization Fit on Affective Commitment. The research design was a field study using survey methodology. The study conducted in a PT. Adira Dinamika Multifinance Bandar Lampung. In this study, the research design included a causal relationship between two or more variables (Fadila, 2020). Judging from the type of data, this study was quantitative research. The study emphasized the analysis of numerical data which were processed by using statistical methods. The research variables consisted of variables: Emotional Intelligence, Person-Organization Fit, and Affective Commitment. All scales used a 5-point agreement – disagreement Likert format. The questionnaires developed for the purpose of isolating factors affecting employee retention. Participants in this study consisted of 66 employees recruited as part of the investigation. A validity test had been done by using the correlation Pearson’s Product-Moment Correlation. Furthermore, the reliability of the questionnaire research used the alpha Cronbach's method. The results of this study were supported by the result of the previous study conducted by (Angga, 2019) and (Solomon, 2019). It stated that Emotional Intelligence did not affect Affective Commitment, Person-Organization Fit affected Affective Commitment. Furthermore, Emotional Intelligence and Person-Organization Fit affected Affective Commitment. This study carried to light original and valuable findings related to the effect of emotional intelligence and person-organization fit after showing expected results in terms of affective commitment.Keywords      :  Emotional Intelligence,Person-Organization Fit, Affective Commitment.